TINGKAT KEJENUHAN BELAJAR SISWA SEKOLAH MENENGAH PERTAMA DI KOTA BANDAR LAMPUNG - Sari, Permata; Kholidin, Farid Imam; Edmawati, Mahmuddah Dewi (LPPM STKIP PGRI Bandar Lampung, 2020)
Burnout is a condition experienced by individuals who are tired of all activities undertaken, so that individuals are not tetarik and do not concentrate on doing the activities being undertaken This study aims to explain the phenomenon or description of burnout learning that occurs in students of junior high school in Bandar Lampung. The design used in this research is descriptive quantitative and the number of sample is 135 students. The results of this study indicate the level of burnout learning of students of junior high school in Bandar Lampung in the medium category, with the number of students is 63 students included in the medium category by a percentage of 46.7%.